147 Oswestry Disability Index Score 3 Months After Elective Lumbar Spine Surgery Does Not Accurately Identify Effective vs Noneffective Spine Care at 12 Months. (August 2015) - Asher, Anthony L.; Chotai, Silky; Devin, Clinton J.; Parker, Scott L.; Sivaganesan, Ahilan; Harell, Frank E.; Hui, Nian; Speroff, Theodore; Dittus, Robert; McGirt, Matthew J.
Abstract : INTRODUCTION: Prospective longitudinal outcomes registries are at the center of evidence-driven health care reform. Obtaining real-world outcomes data at 12 months can be costly and challenging. We analyze whether 3-month outcome measurements suffice to identify effective vs noneffective care for degenerative lumbar surgery. METHODS: Three thousand seventy-three patients undergoing elective spine surgery for degenerative lumbar disease were entered into a prospective multicenter registry (N2QOD). Baseline, 3-, and 12-month follow-up Oswestry Disability Index (ODI) was recorded. Previously published values of minimal clinically important difference (MCID) for ODI-12.8 and substantial clinical benefit (SCB) for ODI-18.8 was utilized. Concordance rate of achieving MCID and SCB for ODI at 3- and 12-months was computed. The absolute difference between 12- and 3-month ODI scores was compared with the absolute differences between 12-month ODI and a multivariable proportional odds logistic regression model-predicted 12-month ODI that took into account the patients' baseline characteristics. RESULTS: Three thousand seventy-three patients undergoing elective spine surgery for degenerative lumbar disease were entered into a prospective multi-center registry (N2QOD). Baseline, 3-, 12-months follow-up ODI was recorded. Previously published values of MCID for ODI-12.8 and SCB for ODI-18.8 was utilized. Concordance rate of achieving MCID and SCB for ODI at 3- and 12-months was computed. The absolute difference between 12- and 3-month ODI scores was compared with the absolute differences between 12-month ODI and a multivariable proportional odds logistic regression model-predicted 12-month ODI. CONCLUSION: The 3-month ODI scores do not accurately estimate the 12-month ODI scores at the individual patient level regardless of the diagnosis and treatment. There is a greater uncertainty in predicting 12-month outcomes when the 3-month outcome is negative. Many patients who do not benefit from surgery by 3 months do so by 12 months, and many report loss of benefit. Prospective longitudinal registries need to span at least 12-months to determine effectiveness of spine care for over 20% of the patients.